Decomposing dynamic profit inefficiency of Belgian dairy farms. (21st September 2017) - Ang, Frederic; Oude Lansink, Alfons
Abstract: This paper introduces a nonparametric framework for analysing dynamic profit inefficiency and applies this to a sample of Belgian, specialised dairy farms from 1996 to 2008. Profit inefficiency is decomposed into technical and allocative inefficiency. The paper also decomposes profit inefficiency into the contributions of output, input, and investment. Finally, the paper identifies the contributions of technical and allocative inefficiency in output, input and investment. The results suggest substantial profit inefficiency under the dairy-quota system, mainly driven by allocative inefficiency of variable input use and output production.